Conceptualization of the social-cultural space in higher school education - Olga V. Yashina (Высшее образование в России, 2022)
It is assumed that the process of higher school second language education is directly associated with social-cultural space, which has a specific effect on this process. Thereby it isessential to interpret matter, structure and content of the developing social-cultural space in the higher school second language learning.